Pemanfaatan Teknologi Augmented Reality Untuk Media Pengenalan Huruf Alfabet Pada Anak Usia Dini - Sinduningrum, Estu; Rosalina, Rosalina; Hilda, Atiqah Meutia (Jurnal SOLMA, 2019)
USAGE OF AUGMENTED REALITY TECHNOLOGY AS AN INTRODUCTION MEDIA OF ALPHABET LETTERS FOR EARLY CHILDHOOD Today, many parents begin to teach their children to early read at home or to educate them at kindergarten school that teaching them to read. The appropriate method of early childhood education are learning while playing. There is no overload and force in this method. Implementation of augmented reality as an introduction media can help children to read happily by scanning the marker that contain of letter or syllables use camera in android software. Animation video, pronunciation audio and 3D animal will appear later in accordance with the letter or syllables and picture in scanned marker. This design then is implemented in an application of android system.  The test of this application was done with both of mitra from Lab School Permata UHAMKA and Baitul Ulum Al Isfahani Manfaluthi attended by teachers and the parents of student guardians. The participant tried to use the application directly and give the feedback how far the application could help the process of learning. Based on evaluation result, this application could help teacher and the parents of guardian student to practice the alphabet learning model fun and happily for student and children.